N, P and K demand in corn lines in the High Valleys of Mexico - González-Molina, Lucila; Virgen-Vargas, Juan; Moreno-Pérez, Esaú del Carmen; de Jesús-Prado, Tranquilino (Revista Mexicana de Ciencias Agrícolas, 2024)
The commercial production of improved corn seed has different limitations, among which the few studies of mineral nutrition of parent lines that form commercial hybrids stand out. This work aimed to determine the demand for N, P and K of corn lines that are parents of hybrids adapted to the conditions of the High Valleys of Mexico and to estimate their fertilization doses with N-P-K. The study was carried out at INIFAP’s Valle de México Experimental Field. The experimental design used was randomized complete blocks in a factorial arrangement with two factors: 1) year of evaluation (2014, 2015 and 2016) and (2) corn lines M-18 (♂-S2), M-55 (♀-S4), M-45 (♂-S3), M-48 (♂-S3) and CML-456 (♂-S4). In physiological maturity, the variables measured were dry matter, grain yield, harvest index and the extraction of N, P and K. The demand and fertilization dose of N, P (P2O5) and K (K2O) (kg ha-1) in the lines were 70 to 115, 0 to 44, 42 to 80; 0, 120 to 249, 0; respectively. The corn lines differed in extractions and the demand for N, P, and K according to the level of inbreeding, plant dry matter production, and grain yield, and consequently in fertilization doses, an aspect that should be considered in a fertilization program for seed production.